Identification of small molecules that support human leukemia stem cell activity ex vivo - Pabst, Caroline; Krosl, Jana; Fares, Iman; Boucher, Geneviève; Ruel, Réjean; Marinier, Anne; Lemieux, Sébastien; Hébert, Josée; Sauvageau, Guy (Nature methods, 2014)
Cancer stem cells, Cell culture, Haematopoietic stem cells, Stem-cell research